Macrophages from naked mole-rat possess distinct immunometabolic signatures upon polarization - Gorshkova, Ekaterina A.; Gubernatorova, Ekaterina O.; Dvorianinova, Ekaterina M.; Yurakova, Taisiya R.; Marey, Maria V.; Averina, Olga A.; Holtze, Susanne; Hildebrandt, Thomas B.; Dmitriev, Alexey A.; Drutskaya, Marina S.; Vyssokikh, Mikhail Yu.; Nedospasov, Sergei A. (Frontiers in Immunology, 2023)
The naked mole-rat (NMR) is a unique long-lived rodent which is highly resistant to age-associated disorders and cancer. The immune system of NMR possesses a distinct cellular composition with the prevalence of myeloid cells. Thus, the detailed phenotypical and functional assessment of NMR myeloid cell compartment may uncover novel mechanisms of immunoregulation and healthy aging. In this study gene expression signatures, reactive nitrogen species and cytokine production, as well as metabolic activity of classically (M1) and alternatively (M2) activated NMR bone marrow-derived macrophages (BMDM) were examined. Polarization of NMR macrophages under pro-inflammatory conditions led to expected M1 phenotype characterized by increased pro-inflammatory gene expression, cytokine production and aerobic glycolysis, but paralleled by reduced production of nitric oxide (NO). Under systemic LPS-induced inflammatory conditions NO production also was not detected in NMR blood monocytes. Altogether, our results indicate that NMR macrophages are capable of transcriptional and metabolic reprogramming under polarizing stimuli, however, NMR M1 possesses species-specific signatures as compared to murine M1, implicating distinct adaptations in NMR immune system.